THE RELATIONSHIP BETWEEN LOCAL FOOD-BASED RECOVERY FEEDING AND OTHER FACTORS ON WEIGHT GAIN IN CHILDREN 12-59 MONTHS OF AGE AT PUSKESMAS CIMPAEUN, DEPOK CITY, INDONESIA, IN 2025 - Sahara, Ghevira Aulia; Rahmawati, Nurul Dina; Triyanti, Triyanti; Fajrinayanti, Fajrinayanti; Pratiwi, Dessy (Ridwan Institute, 2025)
Background: Malnutrition among children aged 12-59 months remains a major challenge in Indonesia, including in Depok City. Local Food-Based Supplementary Feeding (PMT) is one of the government's intervention efforts to improve or recover children's nutritional status. This study aims to determine the relationship between the provision of Local Food-Based Recovery PMT and other factors on toddler weight gain at the Cimpaeun Health Center in Depok City in 2024. Methods: This study used a cross-sectional design with a quantitative approach. The sample consisted of 71 toddlers aged 12-59 months who were purposively selected. Data were collected through questionnaires and secondary data from the health center. Results: The results showed that 60.6% of toddlers experienced adequate weight gain after participating in the Local PMT program. There was a significant association between the appropriateness of the provision of local PMT and weight gain (p = 0.027; OR = 4.464; 95% CI: 1.155-17.252), meaning that toddlers who received inadequate local food-based recovery PMT had a 4.464 times greater risk of underweight gain compared to toddlers who received inadequate PMT. There was a significant association between infection and weight gain (p = 0.015). Infected toddlers had a higher tendency to gain weight. Meanwhile, variables such as diet, mother's education, knowledge, parenting, posyandu visits, and PHBS did not show a significant relationship with toddler weight gain. Conclusions: The provision of an appropriate local food-based recovery PMT and the health condition of the child are the factors most associated with under-five weight gain. Other factors such as infection may encourage more attention from parents, which contributes to children's nutritional recovery.